Recent Lightning-Related Fatalities and Injuries in Bangladesh - Dewan, Ashraf; Hossain, M.; Rahman, M.; Yamane, Y.; Holle, R. (2017)
A database of lightning-related deaths and injuries in Bangladesh was developed from 1990 to mid-2016 from a variety of sources that contains a total of 5468 casualties, composed of 3086 fatalities and 2382 injuries. Spatial, temporal, and demographic aspects of these lightning casualties are evaluated in order to aid relevant entities in effective management of lightning-related meteorological hazards. The annual averages for Bangladesh are 114 fatalities and 89 injuries over the entire period. Weighting by population reveals a fatality rate of 0.92 per million people per year and an injury rate of 0.71. In contrast, the latest 6 years have a fatality rate of 1.6 and injury rate of 1.4. The rural portion of lightning fatalities is 93%. Most fatalities occurred between early morning (0600 LST) and early evening (2000). Through the year, more fatalities occur during the premonsoon season of March through May than during the monsoon season (June–September). The interannual time series of fatalities indicates an increase since the late 2000s, which is a result of greatly improved communications leading to better media reporting of lightning casualties. Bangladesh has also become much more populous in recent years. As a result, the most recent 6 years have 251 fatalities per year, which may be considered as the current estimate. The majority of lightning-related deaths occurred to males. Farming is the major activity at the time of lightning fatalities followed by being inside a dwelling and returning home or walking around homesteads/courtyards.